Fingertip ischemia following intralesional injection of Candida albicans antigen for treatment of a subungual wart - Brogan G.A. Evans; Harry Newman-Plotnick; Adnan Prsic (Dermatology Reports, 2023)
Subungual or periungual cutaneous warts are caused by the Human Papillomavirus (HPV). These lesions can be refractory to destructive therapy, necessitating the use of intralesional immunotherapies such as Candida albicans antigen. In this case report, we present a 23-year-old female who sustained distal fingertip soft tissue necrosis following intralesional injection of Candida albicans antigen for treatment of a refractory subungual wart. While this patient recovered appropriately with conservative bedside debridement and local wound care, intralesional injections to the digit, or hand are not without sequela. Care must be taken to inject intradermal and avoid the underlying digital vasculature. In this case, the radial digital vessels were traumatized upon injection, leading to digital ischemia and soft tissue necrosis. While isolated soft tissue ischemia without compromised perfusion can be treated conservatively, these injuries should be evaluated by a hand surgeon to determine the need for emergent revascularization, or future soft tissue reconstruction.